Unusual stereochemical outcome of radical cyclization: synthesis of (+)-biotin - Chavan, Subhash P.; Chittiboyina, A. G.; Ramakrishna, G.; Tejwani, R. B.; Ravindranathan, T.; Kamat, Subhash K.; Rai, B.; Sivadasan, L.; Balakrishnan, K.; Ramalingam, S.; Deshpande, V. H. (Tetrahedron, 2005)
An enantioselective synthesis of (+)-biotin 1 starting from naturally available cysteine is described. The key steps are the unusual stereochemical outcome of radical cyclization of compound 10 to prepare 5,5-fused system 11, and the introduction of C4-sidechain at C-6 in 13 via a Grignard reaction. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: biotin; exocyclization; radical cyclization

Unusual, selective, reductive, deoxygenation of cyclopentenone alcohols - Bavikar, Suhas R.; Lasonkar, Trupti P.; Chavan, Subhash P.; Borate, Hanumant B. (Tetrahedron Letters, 2014)
A selective, reductive, deoxygenation of 2-aryl-4-hydroxycyclopent-2-en-1-ones to afford 2-aryl-cyclopent-2-en-1-ones was achieved by NaBH4-CeCl3 in methanol. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Cyclopentenone alcohol; Enone; Luche reduction; Reductive deoxygenation